The investigation on mineral wool performance as a potential filter to remove tss in cikapayang river, east jawa, indonesia - Prayogo, Wisnu; Siregar, Januar Parlaungan; Soewondo, Prayatni; Nasution, Zulkifli; Hanami, Zarah Arwieny; Ikhwali, M. Faisi; Estim, Abentin; Suryawan, I. Wayan Koko (Faculty of Environment and Resource Studies,Mahidol University, 2023)
Mineral wool has been used as a filter medium that reaches approximately 95% removal efficiency of total suspended solids (TSS) on a laboratory scale. However, there is no research available has been applied on a larger scale. Hence, this study investigated the ability of mineral wool to remove TSS in two separate segments of the Cikapayang River at different seasons. This analysis utilizes a mineral wool type I, with a dimension of 180×30×120 cm placed in segment 2, and a mineral wool type II with a dimension of 325×30×100 cm placed in segment 9. Samples were taken using the grab sampling method to analyze the TSS concentration before and after being filtered by mineral wool. This investigation concluded that mineral wool could reduce the TSS concentration by up to 65%, and the removal capacity increased by about 6.82% during the dry season. The concentration of TSS in the dry season positively correlates with the increase in the removal capacity of the media. Mineral wool of type I in segment 2 had a better removal ability (31.43%) than type II in segment 9 (14.71%). This research shows that mineral wool can be used as a support material in sanitation sites in large cities experiencing quality degradation in their water bodies.